Neurosurgical Treatment for Drug Addiction: Systematic Review - dos Santos, Patrícia Leonardo Magalhães; Curti, Rafaella Oliveira; da Silva, Ledismar José (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Substance-related disorders are psychiatric conditions that have a worldwide impact. Their multifactorial cycle has been treated pharmacologically and with therapeutic support. However, high refractoriness rates and difficulty to control relapses are among the pitfalls associated with these disorders. Thus, recent studies have shown that deep brain stimulation (DBS) is a promising treatment, with a direct intervention in the neurocircuitry of addiction. The results of the present systematic review of the use of DBS for the treatment of drug addiction show that this surgical procedure can reduce the desire for the drug, and, in some cases, establish abstinence, improve psychiatric symptoms related to mood and quality of life, and reintroduce the patient into the social and family environments. Nevertheless, this approach is still limited to the academic realm, based mainly on case reports, with ethics and therapeutic protocols still to be defined. Further in-depth scientific investigations are required to recommend its clinical application.
Keywords: substance-related disorders; deep brain stimulation; systematic review